ANALISIS FAKTOR KEGAGALAN PROMOSI KESEHATAN DALAM PEMBERIAN ASI EKSKLUSIF OLEH IBU BEKERJA - Ardi Yansyah (Universitas Fort De Kock, 2020)
The achievement of exclusive breastfeeding as a global strategy to reduce IMR (Infant Mortality Rate) is still around 35.73% nationally. Jambi City ranks the lowest in the coverage of exclusive breastfeeding in Jambi Province (30.4%) in 2017. Several reasons are the reasons why mothers do not provide exclusive breastfeeding, including mother's employment status, incessant promotion of breastfeeding substitutes, and lack of husband and family support. In working mothers, breastfeeding is a behavior that can be influenced by multidimensional influences on the success or failure of health promotion. This study aims to analyze the factors that influence the failure of health promotion, namely sociodemography, psychosocial and postnatal care towards exclusive breastfeeding by working mothers in Jambi City. Quantitative research method with cross-sectional design, using a questionnaire instrument to 105 working mothers who have children aged 6-24 months in Jambi City from April to May 2020. The selection of respondents was based on purposive sampling. Data were analyzed using the chi-square test. The results showed there was an effect of sociodemography (Pvalue 0.003), psychosocial (Pvalue 0.001), and postnatal (Pvalue 0.000) on exclusive breastfeeding by working mothers in Jambi City. Psychosocial and postnatal factors have several dominant indicators affecting working mothers not exclusively breastfeeding, including the allocation of working time and feeding formula or complementary breastfeeding aged <6 months.